Genotypic portrait of SARS-CoV-2 in Primorsky Krai during the COVID-19 pandemic - Anna Y. Popova; Mikhail Y. Shchelkanov; Natalia V. Krylova; Alexey A. Belik; Lyubov M. Semeikina; Tatyana S. Zaporozhets; Vyacheslav Y. Smolenskiy; Elena V. Persianova; Marina N. Prosyannikova; Yuriy A. Belov; Olga V. Iunikhina; Anastasiya B. Pott; et al. (Журнал микробиологии, эпидемиологии и иммунобиологии, 2024)
Introduction. The COVID-19 pandemic, etiologically related to SARS-CoV-2, was the longest-lasting pandemic for an acute respiratory disease and had a significant impact on demography, economics and politics globally. Experiences with this pandemic are significant for the sustainable development of human society. A detailed analysis of these experiences in epidemic control should include details of the pathogen evolution down to the regional level.